In dubious battle - Steinbeck, John, 1902-1968. (New York : Penguin, 1992)
Migratory workers strike against the landowners in California's apple country, led by Jim Nolan.
Includes bibliographical references (p. xxxi).
Wilson's Fiction.
Young Adult
Keywords: Migrant agricultural laborers -- California -- Fiction; Strikes and lockouts -- California -- Fiction; Agricultural laborers -- Fiction; Migrant labor -- Fiction; Strikes -- Fiction; California -- Fiction